(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
In addition to economic and organizational measures for the development of poultry in the world, scientific research is being conducted on the health of poultry and their environment. The negative impact of helminthiasis on the development and productivity of poultry, including parasitic worms, found in the wild rabbits, requires special research in its prevention.Wild chickens and poultry, especially helminthiasis in chickens (ascariasis, heteracidosis, echinostomatidosis, rayetinosis, hymenolepidosis, hoanoteniosis, capillaries, etc.) are the most common cause of pests in many countries, including the economy of poultry. Therefore, it is important to identify the diversity, biology, ecology and distribution of helminth species, and to develop measures to combat and prevent them.